Analysis of the Implementation of the Batumbang Apam Ritual in Malay Ethnic Weddings in Banjar Serasan - Utami, Fadhira; Imran, Imran; Astari, Zuri; Sikwan, Agus (Universitas Tanjungpura, 2025)
The purpose of this research is to understand the implementation of the Batumbang Apam ritual in Malay ethnic weddings in Banjar Serasan Subdistrict, East Pontianak District, using a descriptive qualitative approach. The study involved three informants: one key informant and two supporting informants. The findings indicate that the Batumbang Apam ritual consists of three stages. The initial process includes preparing and cleaning coconut fronds and sugarcane stalks, preparing apam cakes and other complementary cakes, and arranging seven sheets of fabric for the bride and groom to sit on. The core process involves reciting the Yasin prayer and circling the coconut fronds seven times in succession. The final process consists of a collective prayer led by the ritual guide and communal dining with invited guests. The ritual serves several functions: socially, it strengthens family bonds through mutual assistance and togetherness; religiously, it reinforces faith in Allah, seeking His blessings for safety and smooth proceedings; and environmentally, it highlights the use of natural elements such as water, air, trees, and soil, with coconut fronds and sugarcane stalks symbolizing divine creation. Symbolically, the apam cake, with its sweetness, softness, and richness, represents the hope that these qualities will be present in the couple's married life, while the strong and resilient nature of coconut fronds symbolizes the wish for the couple to have endurance and longevity in their marriage.